2017
DOI: 10.1016/j.ghir.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal exercise training and protein-pacing enhances physical performance adaptations independent of growth hormone and BDNF but may be dependent on IGF-1 in exercise-trained men

Abstract: Exercise-trained men consuming a P diet combined with multi-component exercise training (PRISE) enhance muscular power, strength, aerobic performance, and flexibility which are not likely related to GH or BDNF but possibly to IGF-1 response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“… Gusdon et al (2017) suggested that exercise training in old mice could improve brain mitochondrial function by affecting electron transport chain function and mitochondrial dynamics without increasing mitochondrial biogenesis. Exercise-trained men consuming a protein-pacing diet along with multicomponent exercise training (PRISE) improved muscular power, strength, and flexibility ( Ives et al, 2017 ). These effects of exercise are not likely related to growth hormone or BDNF but possibly related to IGF-1 response ( Ives et al, 2017 ).…”
Section: Exercise and Energy Restrictionmentioning
confidence: 99%
“… Gusdon et al (2017) suggested that exercise training in old mice could improve brain mitochondrial function by affecting electron transport chain function and mitochondrial dynamics without increasing mitochondrial biogenesis. Exercise-trained men consuming a protein-pacing diet along with multicomponent exercise training (PRISE) improved muscular power, strength, and flexibility ( Ives et al, 2017 ). These effects of exercise are not likely related to growth hormone or BDNF but possibly related to IGF-1 response ( Ives et al, 2017 ).…”
Section: Exercise and Energy Restrictionmentioning
confidence: 99%
“…Evidence has surfaced that suggests what part of the day the majority of calories are consumed may affect one’s health, weight loss or body composition changes. As a starting point, it is important to highlight that most of the available research on this topic has largely used non-athletic, untrained populations except two recent publications using trained men and women [ 129 , 130 ]. Whether or not these findings apply to highly trained, athletic populations remains to be seen.…”
Section: Introductionmentioning
confidence: 99%
“…Whether acute MPS responses translate to longitudinal changes in hypertrophy or fiber composition also remains to be determined [ 120 ]. In addition to these aforementioned studies, extensive work by Arciero and colleagues has directly examined the combined effect of meal frequency and timing along with the distribution of protein intake with [ 129 , 130 , 152 156 ] and without [ 157 , 158 ] exercise training in both short-term (3 months) and longer-term (> 1 year) interventions using a “protein pacing” model. Protein pacing involves the consumption of 20–40 g servings of high-quality protein, from both whole food and protein supplementation, evenly spaced throughout the day, approximately every 3 h. The first meal is consumed within 60 min of waking in the morning, and the last meal is eaten within 3 h of going to sleep at night.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were healthy and not resistance trained for at least years. Exclusion criteria included smoking during the last year, use of nutritional supplements or supplemental androgens within the last 6 months, current use of statins, recent history of cancer (within 2 years), any metabolic disorder including known electrolyte abnormalities; heart disease, arrhythmias, diabetes, thyroid disease, or hypogonadism and any absolute contraindications to exercise according to American College of Sports Medicine (ACSM) guidelines [18]. Following the informational session, participants completed a medical history questionnaire and signed a written consent form.…”
Section: Participantsmentioning
confidence: 99%